PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION PADA PEMBELAJARAN IPAS MATERI MATA PENCAHARIAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI DANAU INA OESAPA - Beatrix Ramona Manafe; Treesly Y. N. Adoe; Adam B. N. Benu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Research conducted by Beatrix Ramona Manafe, Student Identification Number (NIM) 2201140097, entitled “The Implementation of the Student Teams Achievement Division (STAD) Cooperative Learning Model in IPAS Learning on Livelihood Materials to Improve the Learning Outcomes of Fourth-Grade Students at SD Negeri Danau Ina Oesapa.” The question explored in this study is how the implementation of the STAD cooperative learning model in IPAS learning on livelihoods and community professions can improve the learning outcomes of fourth-grade students at SD Negeri Danau Ina Oesapa.The objective of this study is to determine the implementation of the STAD cooperative learning model in IPAS learning on livelihoods and community professions to improve the learning outcomes of fourth-grade elementary school students. Various methods were used for data collection, including observation, tests, and documentation. The participants involved in this study consisted of 29 students, including 15 male students and 14 female students.This study was conducted at UPTD SD Negeri Danau Ina Oesapa using a Classroom Action Research (CAR) approach consisting of two cycles. Each cycle included the stages of planning, action, observation, and evaluation. The findings showed that in Cycle I, only 6 students (20.69%) achieved mastery, while 23 students (79.31%) had not yet achieved mastery.Furthermore, in Cycle II, students’ learning outcomes improved significantly. The results indicated that 25 students (86.20%) achieved mastery, while 4 students (13.80%) had not yet achieved mastery. The implementation of the STAD cooperative learning model was able to increase students’ activeness, cooperation, and participation in the learning process, thereby contributing to improved understanding of the material and enhanced learning outcomes.This study was conducted at UPTD SD Negeri Danau Ina Oesapa using a Classroom Action Research (CAR) approach with two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The findings indicated that in Cycle I, only 6 students (20.69%) met the mastery criteria, while 23 students (79.31%) remained below the established standard.